Diffusion-limited currents to nanoparticles of various shapes supported on an electrode; Spheres, hemispheres, and distorted spheres and hemispheres - Streeter, I; Compton, R (2007)
The finite difference method is used to simulate the current at a spherical nanoparticle sitting upon a planar electrode, assuming electrolysis occurs only at the nanoparticle surface. The accuracy of the simulation technique is confirmed by using the same approach to simulate a hemispherical electrode. Nanoparticles with the geometry of a distorted sphere or hemisphere are also considered. Equations are given for the corresponding masstransport-limiting current. For the spherical nanoparticle, this expression is ilim = -8.71nFZ)rs[A]bulk, where D is the diffusion coefficient, rs is the radius of the particle, [A]bulk is the bulk concentration of the electroactive species, and n is the number of electrons transferred. © 2007 American Chemical Society.